WE2.8 Improving Management for Acute Cholecystitis and Biliary Pancreatitis – the 'Hot Gallbladder Pathway'. (9th August 2022) - Kam, Cheuk Tung; Abdelsaid, Kirolos; Jayasankar, Balaji; Balasubramaniam, Dinesh; Abdulaal, Yasser
Abstract: Aim: There is a wide variation between National Health Service (NHS) hospitals in the management of patients with acute cholecystitis and biliary pancreatitis. 20–33% of patients will make repeat visits to hospital with gallstone-related symptoms before any surgical intervention performed. We established a 'Hot Gallbladder Pathway' with the aim for improving outcome and decreasing complications of these patients. The aim of this quality improvement project was to assess if a district general hospital (DGH) could provide a safe and effective 'hot gallbladder' service with a clear pathway. Method: Quality improvement methods were used to integrate the 'hot gallbladder pathway' to manage patients with acute calculous cholecystitis and biliary pancreatitis. A prospective observational study with strict inclusion/ exclusion criteria and secure online data was conducted during a 13-month period. The data were then compared against existing National Institute for Health and Clinical Excellence (NICE) guidelines and further changes were recommended. Results: We achieved almost 70% of the patients undergoing emergency laparoscopic cholecystectomy in both group of patients who met the pathway criteria within the expected time frame, compared with the pre-implementation result of 23% and national average of only 16% in England. None of the patients suffered from intraoperative complications or 30-day mortality. Conclusion: A clear 'hot gall bladder pathway' is effective at improving care for patients requiring emergency laparoscopic cholecystectomy and potentially useful for other acute Trusts which their standard is below the NICE guideline.